Synthesis and polymerization of epoxidized soybean oil - diamino silane adducts - Akdemir, Melissa. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
In this study, Epoxidized Soybean oil is reacted with a diamino-functional silane, N-2-aminoethyl-3-Aminopropyltrimethoxysilane, through ring opening of the epoxide. This was done in three different stoichiometry where tertiary amine:epoxide ratios were 0.5, 0.7 and 1.0. The adducts were characterized by NMR and IR spectroscopy. Resulting adducts were then moisture cured on a glass surface at room temperature, and were polymerized via self-condensation at room temperature. All the samples were post-cured at 150˚C for 1hour. Cured products, both on glass surface and the self-condensation products were characterized with IR spectroscopy. Mechanical properties of the self-condensation products were analyzed with DMA (Dynamic Mechanical Analysis) and also Tensile strength was measured. Surface hardness tests, swelling tests, adhesion tests and contact angle measurements were done on the treated glass surfaces. As the silane ratio increases, the mechanical strength increases for applications on glass surface and the selfcondensation products.
Keywords: Soy oil.; Epoxy compounds.; Biodegradation.